The Relevance of Ki Hajar Dewantara's Educational Thought to the Curriculum 13 - Endang Trisiana (Penerbit Hellow Pustaka, 2023)
Education is the key to the development of the country. Ki Hajar Dewantara, an influential figure in education thinking in Indonesia, introduced the concept of